AniraBlock: A leap towards dynamic smart contracts in agriculture using blockchain based key-value format framework - Saputra, Irwansyah; Arkeman, Yandra; Jaya, Indra; Hermadi, Irman; Akbar, Nur Arifin; Sutedja, Indrajani (Communications in Science and Technology, 2023)
Blockchain technology offers data transparency and traceability, which is particularly useful in the agricultural sector, especially within the supply chains of commodities like coffee and fish. This sector often encounters issues such as quality degradation, unclear information, and socioeconomic injustice affecting stakeholders. The implementation of Static Smart Contracts (SSCs) on blockchains provides a structured method for executing agreements. However, this approach also has limitations, including a lack of flexibility and responsiveness to dynamic changes in the supply chain. Despite these challenges, blockchain remains a valuable tool for ensuring transaction transparency, traceability, and integrity, which are vital in agriculture. These limitations involve unchangeable parameters, rigid rules, and constraints on adaptability and scalability. This study aims to tackle these issues by designing a more dynamic and responsive smart contract system. We introduce AniraBlock, a revolutionary concept for the agricultural supply chain, particularly in the coffee and fish sectors, by implementing Dynamic Smart Contracts (DSCs) based on a key-value format framework. Unlike SSCs, DSCs offer enhanced adaptability and scalability, addressing the former's limitations. Our study adopts a mixed-method approach, utilizing both qualitative and quantitative data to validate AniraBlock's effectiveness. Preliminary results show significant improvements in data management and supply chain transparency. The proposed framework has the potential to influence the agricultural sector by boosting data integrity and operational efficiency.